2016
DOI: 10.1007/s10548-016-0495-1
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances of Agency and Ownership in Schizophrenia: An Auditory Verbal Event Related Potentials Study

Abstract: A 'sense of self' is essentially the ability to distinguish between self-generated and external stimuli. It consists of at least two very basic senses: a sense of agency and a sense of ownership. Disturbances seem to provide a basic deficit in many psychiatric diseases. The aim of our study was to manipulate those qualities separately in 28 patients with schizophrenia (14 auditory hallucinators and 14 non-hallucinators) and 28 healthy controls (HC) and to investigate the effects on the topographies and the pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In other words in HC, self-generated (and therefore highly predictable) sounds give rise to suppressed responses, thus allowing speakers to pay better attention to sounds in the external environment [ 35 , 37 ], indicative of a primordial biological basis for self-agency that is essential for normal interactions with outside reality [ 37 , 39 , 40 ]. By contrast, in SZ, reduced suppression to self-generated actions (i.e., during speaking, for example) [ 31 , 37 , 41 43 ] suggests patients may have noisier auditory cortical signal to begin with, making it more difficult to make reliable computations about the comparisons between predicted and actual auditory feedback while speaking. This auditory cortical signal is sent to higher order regions within PFC/mPFC [ 12 , 36 ] that are considered to be critical for computing the reliance that needs to be placed on self-predictions [ 12 ], in order to mediate higher-order agency judgments [ 19 , 20 ].…”
Section: Self-prediction Mechanisms Are Impaired In Schizophreniamentioning
confidence: 99%
“…In other words in HC, self-generated (and therefore highly predictable) sounds give rise to suppressed responses, thus allowing speakers to pay better attention to sounds in the external environment [ 35 , 37 ], indicative of a primordial biological basis for self-agency that is essential for normal interactions with outside reality [ 37 , 39 , 40 ]. By contrast, in SZ, reduced suppression to self-generated actions (i.e., during speaking, for example) [ 31 , 37 , 41 43 ] suggests patients may have noisier auditory cortical signal to begin with, making it more difficult to make reliable computations about the comparisons between predicted and actual auditory feedback while speaking. This auditory cortical signal is sent to higher order regions within PFC/mPFC [ 12 , 36 ] that are considered to be critical for computing the reliance that needs to be placed on self-predictions [ 12 ], in order to mediate higher-order agency judgments [ 19 , 20 ].…”
Section: Self-prediction Mechanisms Are Impaired In Schizophreniamentioning
confidence: 99%
“…Furthermore, altered effective connectivity between the left superior temporal and anterior cingulate cortex is associated with the tendency to perceive one's own voice as generated by another person (Mechelli et al, 2007). Altered function of the anterior cingulate cortex may hence contribute to a decreased sense of agency over the sensory consequences of one's own actions (Asai and Tanno, 2013;Bühler et al, 2016;Sugimori et al, 2011). Accordingly, the self-generated voice would be evaluated as external ('this is not my voice') in voice hearers (Allen et al, 2006(Allen et al, , 2004Brébion et al, 2016;Johns et al, 2010;Pinheiro et al, 2016).…”
Section: Altered Self-awareness and Agency?mentioning
confidence: 99%
“…Mathalon et al (39) found that reduced N100 suppression was correlated with unusual thought content in one of two patient groups. Bühler et al (34), by contrast, found no correlation between Positive and Negative Syndrome Scale (PANSS) scores and either N100 amplitude or the amplitude of an unidentified "late component" that appears to be a P200. Perez et al (40) likewise found no correlation between N100 suppression and any of four psychopathology subscales.…”
Section: Event-related Potentials Datamentioning
confidence: 96%